Influence of the grip width on the reliability and magnitude of different velocity variables during the bench press exercise - Pérez-Castilla, A.; Martínez-García, D.; Jerez-Mayorga, D.; Rodríguez-Perea, A.; Chirosa-Ríos, L. J.; García-Ramos, A. (European Journal of Sport Science, 2020)
This study aimed to compare the within-session reliability and magnitude of velocity variables recorded against a range of submaximal loads during the bench press (BP) exercise performed in a Smith machine using different grip widths. Sixteen physically active men (BP one-repetition maximum [1RM] relative to body mass = 1.01 ± 0.19 kg·kg-1) were randomly tested on 4 sessions using a close grip width (100% of biacromial width), medium grip width (150% of biacromial width), wide grip width (200% of biacromial width), and self-selected grip width (176 ± 17% of biacromial width). Mean velocity (MV), maximum velocity (Vmax), and vertical displacement were recorded with a linear velocity transducer against the 35%1RM, 55%1RM, and 75%1RM. The main findings revealed that (I) the self-selected was the only grip width with an acceptable reliability for all loads and velocity variables (CV = 7.56%; ICC = 0.82), (II) the medium grip width provided the highest reliability for MV (CV ratio = 1.20), while a comparable reliability was observed for Vmax using the close, medium and self-selected grip widths (CV ratio = 1.08), (III) the Vmax showed the highest reliability for all grip widths (CV ratio = 1.68), and (IV) the MV and vertical displacement of the barbell were generally higher for narrow grip widths (close and medium) compared to the wide and self-selected grip widths, while no significant differences between the grip widths were observed for Vmax (p > .05). Taken together, we recommend the assessment of Vmax using a self-selected grip width during the routine testing of BP performance against submaximal loads.